Do Asset Prices in Transition Countries Contain Information About Future Economic Activity? - Sloek, Torsten (IMF Working Papers; Working Paper, 2000)
There is ample empirical evidence for developed economies that asset prices contain information about future economic developments. But is this also the case in transition economies? Using a panel of monthly data for the Czech Republic, Hungary, Poland, Russia, Slovakia, and Slovenia for the period 1994-1999 it is shown that historical values for interest rates, exchange rates, and stock prices signal future movements in real economic activity. This result has significant implications for policymakers, and a composite leading indicator based on the three asset prices is presented, which contains information about the future development of economic activity.